Endometrial tuberculosis mimicking endometrial malignancy - histopathology key to management¬ - a case report - Kanili Jimo; Nounechutuo Miachieo; Bendangtoshi Jamir; Rebeki Momin; Nito Yepthomi (Barpeta Obstetrics and Gynaecological Society, 2023)
Endometrial tuberculosis may mimic endometrial malignancy in clinical presentation, ultrasound findings and laboratory tests. We present a case of genital tuberculosis where a provisional diagnosis of endometrial carcinoma was made initially. Patient was later diagnosed and treated with standardized anti tubercular drugs (ethambutol, isoniazid, pyrazinamide and rifampicin). Patient had clinical improvement and normal endometrial thickness at the end of the treatment. This case underlines the mandatory need of a high index of suspicion in our country, towards pelvic tuberculosis preoperatively in a patient with endometrial hyperplasia and ascites.